Optimization of batch study parameters for the adsorption of lead(II) ions onto spent tea grains - Chauhan, Surendra Singh; Dikshit, Prabhat Kumar Singh (IWA Publishing, 2023)
The present study aims to investigate the use of response surface methodology (RSM) modelling and experimental investigation for the optimization of lead(II) adsorption onto spent tea grains (STG). Independent process variables were optimized and found to be in the range of 38.75 mg/l (initial concentration), 5.20655 (pH), 119.32 rpm (stirring speed), and 3.25 g/l (STG dose) for a contact time of 135.05 min. The optimum adsorption capacity was found to be 8.9087 mg/g through RSM modelling with a maximum of 18.146 mg/g. The batch study was performed by varying different parameters: pH (2.0–7.0), initial concentration (5–50 mg/l), dose (0.1–1 g/100 ml), contact time (15–180 min), and stirring speed (30–200 rpm). The characterization STG was done by proximate and ultimate analysis, FTIR spectroscopy, XRD analysis, thermogravimetric analysis (TGA), and SEM-EDX. By fitting equilibrium data onto Langmuir isotherm model, the maximum adsorption capacity was found to be 24.272 mg/g. The optimum pH found for lead(II) adsorption onto STG was 5. At optimum conditions, the maximum removal efficiency of STG for lead(II) ions’ adsorption is 94.33%. Based on the findings it is safe to conclude that the STG could be used as a potential adsorbent.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: adsorption; agricultural waste; biosorbent; equilibrium isotherms; heavy metal; kinetics; spent tea grains